The Effectiveness of the Singing Method on Knowledge of Brushing Teeth in Mentally Disabled Children at SLB Paedagogia Surabaya in 2023 - Dewi De Fatimah; I.G.A. Kusuma Astuti N.P; Bambang Hadi Sugito; Silvia Prasetyowati (International Journal of Advanced Health Science and Technology, 2023)
One of the effects of a lack of knowledge about how to maintain dental hygiene is having dental health problems such as cavities. Provision of health education can increase health knowledge. In certain circumstances, especially in mentally retarded children, the health of their teeth and mouth is neglected. A study has shown that mentally retarded children have a risk of poor dental and oral health. It is important for mentally retarded children to gain knowledge, so they can take care of and develop themselves. The problem in this study is the lack of knowledge about brushing teeth in mentally retarded children at SLB Paedagogia Surabaya. This study aims to determine the effectiveness of the singing method on knowledge about brushing teeth in mentally retarded children at SLB Paedagogia Surabaya. This type of research is a true experiment with a pretest-posttest design with a control group, with research subjects as many as 30 mentally retarded children who were divided into 2 groups. The data collection instrument used was a questionnaire. The data analysis technique uses the Wilcoxon test and the Mann-Whitney test. There is the effectiveness of the singing method on knowledge about brushing teeth in mentally retarded children at SLB Paedagogia Surabaya in 2023.